2019
DOI: 10.3126/jbpkihs.v2i1.24962
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude towards Basic Life Support among Health Care Professionals Working in Emergency of BPKIHS

Abstract: Background: Basic Life Support (BLS) aims to maintain respiration and circulation in the cardiac arrest victim and involves a major focus on cardiopulmonary resuscitation (CPR) with minimal use of ancillary equipment. The raised standards of care demand that knowledge about BLS/ CPR be updated and include the lay persons as well as medical experts who have the potential to become the teachers of the skill. The objective of the study was to describe the knowledge and attitude of medical personnel (nurses and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…It is a specific level of prehospital medical care provided by the trained responders, including emergency medical technicians, in the absence of advanced medical care to minimize the patient's critical condition. BLS course trains participants to promptly recognize several life-threatening emergencies, give high-quality chest compressions, deliver appropriate ventilations, and provide early use of an automated external defibrillator (AED) [ 2 ]. Basic Life Support (BLS) is a lifesaving intervention in a premedical facility.…”
Section: Introductionmentioning
confidence: 99%
“…It is a specific level of prehospital medical care provided by the trained responders, including emergency medical technicians, in the absence of advanced medical care to minimize the patient's critical condition. BLS course trains participants to promptly recognize several life-threatening emergencies, give high-quality chest compressions, deliver appropriate ventilations, and provide early use of an automated external defibrillator (AED) [ 2 ]. Basic Life Support (BLS) is a lifesaving intervention in a premedical facility.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out in Nepal also correlated the positive attitude of participants with the seniority and experience of healthcare professionals. 26 Analysis of our study revealed that the gender of the participant had no remarkable association with the attitude of an individual (p=0.157). This finding was in contradiction to the results of a study carried out by Krammel et al, 27 which concluded that the female gender had a poor attitude when compared with their colleagues.…”
Section: Discussionmentioning
confidence: 65%
“…This finding was in contradiction with a study carried out in Nepal which showed that increasing the age of participants was linked with a more positive outlook towards BLS and its training. 26 …”
Section: Discussionmentioning
confidence: 99%
“…These findings are echoed in studies from other countries, such as Italy and Afghanistan, where discrepancies in BLS knowledge and competence were observed between doctors and nurses, often favoring the former in terms of theoretical understanding (15) (16). Conversely, some studies have reported that both nurses and physicians possess adequate knowledge and show a positive attitude towards performing BLS, suggesting a correlation between increased age and a better disposition towards BLS practices (20). This comprehensive analysis of the current state of BLS knowledge, attitude, and practice among healthcare professionals, particularly in the context of Peshawar, Pakistan, underscores the critical need for systematic training and education in BLS techniques.…”
Section: Introductionmentioning
confidence: 83%